Revisioning Buddhism as a Science of the Mind in a Secularized China: A Tibetan Perspective - Suodaji, Kanbu (Journal of global buddhism, 2017)
Tibetan Buddhism is one of the fastest growing religions among Chinese in the twenty-first century. The transnational teaching activities of numerous Tibetan lamas attest to this religious trend in the popular realm of contemporary China. Unlike on their native soil, Tibetan lamas immersed in urban China encounter converts whose acceptance of Buddhism often rests upon a “scientific” assessment of Buddhism. Thus, the Buddhism-science dialogue stands out as a central theme in contemporary Sino-Tibetan Buddhist encounters. Based on the authors’ collaborative study of the Buddhism-science entanglement in this transnational Buddhist context, this article will illustrate that science signifies not merely the conventionally accepted system of knowledge, based on the modern, empirically-driven search for the understanding of the material world. Instead, it connotes a web of interconnected social meanings pertaining to Buddhist understanding, critique, and appropriation of this web. In this regard, the authors argue that simultaneously, science is identified as an integral part of the iconoclastic secularism in modern China subject to contemporary Buddhist critique, science is utilized as an instrument of Buddhist conversion, and science is reconceived as a neutral, open social space for knowledge making, in which an increasing number of Buddhist teachers persistently claim Buddhism as a science of its own.